Betting on freedom : my life in the church - Geninazzi, Luigi, 1947-; Lancellotti, Carlo, 1965- (The Catholic University of America Press, 2021)
"In this wide-ranging conversation with the Italian journalist Luigi Geninazzi, Cardinal Angelo Scola discusses both the salient moments of his own life and the path and situation of the Church and society in Europe over the last half-century. The Cardinal recounts his life, speaking of the extraordinary gift of particular friendships he has had, starting with Luigi Giussani, founder of the ecclesial movement Communion and Liberation (CL), and moving on to discuss Hans Urs von Balthasar, Henri De Lubac, and Joseph Ratzinger. A figure who bridges the past three pontificates, Scola discusses his relationships with St. John Paul II, by whom he was nominated a bishop at the relatively young age of forty nine; Benedict XVI, with whom he has had an intense intellectual friendship for decades; and Pope Francis, of whom he speaks with affection and hope"--